Optimization of the cost structure for hydropower generation: An application of the Black Litterman Model [Optimización de la estructura de costos para la generación de energía hidroeléctrica: Una aplicación del Modelo Black Litterman] (2017)
In this paper the expectations of energy generators in the market about costs under a context of uncertainty are modeled through the application of discounted cash flows and the Black Litterman model. Models of Seasonal Auto Regressive Integrated Moving Average (SARIMA) and Autoregressive Conditional Heteroskedasticity are used to determine the variables behavior that determines the income and expenses of a hydroelectric project in a small power plant. Obtaining the optimal combination of financing sources and energy amounts generated to obtain expected return, satisfy demand in the conditions required by law and meet market expectations. © 2017. revistaESPACIOS.com.